Correction: Bowers et al. Tart Cherry Extract and Omega Fatty Acids Reduce Behavioral Deficits and Gliosis in the 5xFAD Mouse Model of Alzheimer’s Disease. Brain Sci. 2021, 11, 1423 - Zackary Bowers; Panchanan Maiti; Ali Bourcier; Jarod Morse; Kenneth Jenrow; Julien Rossignol; Gary L. Dunbar (Brain Sciences, 2023)
There is an error in the title of the published paper [...]